Pengaruh Variabel Akuntansi dan Data Pasar terhadap Resiko Persepsian (Perceived Risk) Saham pada Perusahaan Publik yang Terdaftar di BEJ - AIDA AINUL MARDIYAH; NUR INDRIANTORO (The Indonesian Journal of Accounting Research, 2013)
This study intends to identify the effects of  dividend pay out ratio, current ratio, asset size, asset growth, leverage, earnings variability, earnings covariability, and market’s beta on the perceived risk of the stocks. Data is selected using stratified random sampling. The analysis units for the eight independent variables are 72 companies registered on the Jakarta Stock Exchange from 1993-1996, and the analysis unit of the dependent variable is broker who analyzed the perceived risk. The data collection for the perceived risk (DV) is conducted by using mail survey while for the dividend pay out ratio, current ratio, asset size, asset growth, leverage, earnings variability, earnings covariability, and market’s beta (IV) are from archival. The statistic method used to test the hypotheses is MDA (Multiple Discriminant Analysis).The study results are as follows: first, perceived risk is valid as the substitute for market’s beta; second, there are no differences across industries (i.e., service, manufacturing, and trading industries);  third, four of the  eight independent variables, i.e. dividend pay out ratio, asset growth, leverage, and earnings covariability do not support hypotheses. Therefore it can be concluded that there is no effect of dividend pay out ratio, asset growth, leverage, and earnings covariability  on the perceived risk, whereas the hypotheses supporting the theory are current ratio, asset size,  earnings variability, market’s beta, and   hypotheses two.